Instructional design concepts, methodologies, tools and applications. (Hershey, Pensylvania Information Science Reference, 2011)
Presents a complete overview of historical perspectives, new methods and applications, and models in instructional design research and development.
Section 1. Fundamental concepts and theories--Section 2. Development and design methodologies--Section 3. Tools and technologies--Section 4. Utilization and application--Section 5. Organizational and social implications--Section 6. Managerial impact--Section 7. Critical issues--Section 8. Emerging trends.
Electronic reproduction.
Keywords: Instructional systems -- Design